2020
DOI: 10.1039/d0cc04415f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of β- and γ-lactam fused dihydropyrazinones from Ugi adducts via a sequential ring construction strategy

Abstract: A modular approach for the construction of β- and γ-lactam fused dihydropyrazinones from the readily available Ugi adducts has been described. The sequencial construction of rings through base-mediated cycloisomerization followed...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…In this direction, our group demonstrated the regioselective construction of β‐ and γ‐lactam fused dihydropyrazinones 53 and 54 from alkynoic acid‐derived Ugi adducts 52 (Scheme 17). [26] The sequential construction of rings through base‐mediated cycloisomerization, followed by acid‐mediated cyclization, yielded β‐lactam fused dihydropyrazinones 53 in a 4‐ exo‐dig fashion. However, the Ugi‐derived dihydropyrazinones afforded γ‐lactam fused dihydropyrazinones 54 under base‐mediated cycloisomerization in a 5‐ endo‐dig manner.…”
Section: Base‐mediated Post‐ugi Transformationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this direction, our group demonstrated the regioselective construction of β‐ and γ‐lactam fused dihydropyrazinones 53 and 54 from alkynoic acid‐derived Ugi adducts 52 (Scheme 17). [26] The sequential construction of rings through base‐mediated cycloisomerization, followed by acid‐mediated cyclization, yielded β‐lactam fused dihydropyrazinones 53 in a 4‐ exo‐dig fashion. However, the Ugi‐derived dihydropyrazinones afforded γ‐lactam fused dihydropyrazinones 54 under base‐mediated cycloisomerization in a 5‐ endo‐dig manner.…”
Section: Base‐mediated Post‐ugi Transformationsmentioning
confidence: 99%
“…Our research group is actively engaged in exploring novel post‐Ugi transformations [21–25] and recently, we have been working on base‐mediated post‐Ugi transformations to access novel bioactive compounds for drug discovery [26–29] . Encouraged by our findings and related research worldwide, we present an exciting review highlighting the base‐mediated post‐Ugi transformations by trapping the peptidyl anion.…”
Section: Introductionmentioning
confidence: 96%
“…2). 27 Inspired by previous reports and in continuation of our ongoing efforts to identify medicinally important structural frameworks, [28][29][30][31][32][33][34][35][36] a series of N-alkylated pyrroloquinolinone derivatives were designed and synthesized, and their antileishmanial efficacy was evaluated against visceral leishmaniasis (VL).…”
Section: Introductionmentioning
confidence: 99%
“…4 From similar Ugi adducts, the Srivastava group reported that this reaction could occur at room temperature in the presence of NaH. 5 The Van der Eycken group also published their ndings that a g-lactam core could be constructed under different conditions. 4b,6 Besides the C-C bond formation, the Zhang group reported a C-N bond formation protocol to build piperazine-2,5-dione core through alkyne and amide groups (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%